Confirmatory Factor Analysis of the Personal Growth Initiative Scale-II in Indonesian Women Leaders - Dhini Rama Dhania; Fendy Suhariadi; Fajrianthi Fajrianthi (Psympathic : Jurnal Ilmiah Psikologi, 2022)
This study aimed to examine the 16 items of the Personal Growth Initiative Scale-II (PGIS-II) psychometric traits among women holding corporate leadership positions in Indonesia. It used quantitative methods and was conducted on 181 women in various management positions. Confirmatory factor analysis (CFA) was used to analyze the PGIS-II instrument factorial validity comprising four dimensions and to determine the factor structure suitability. Furthermore, internal reliability and convergent validity were analyzed from the total and subscale scores. The results showed that the maximum likelihood estimation (MLE) matched scores with different ranges. PGIS-II's internal reliability indicated the intentional planning dimensions and behavior that require modifying the items’ measurement and analysis. In terms of validity, the Intentional Behavior (IB2) indicator does not meet the standard loading factor (SLF). However, these findings suggest that the PGIS-II scale could be used to study female figures in Indonesia.